Amphimedon species (Porifera: Niphatidae) from the Gulf of Aqaba, Northern Red Sea: Filling the gaps in the distribution of a common pantropical genus - Helmy, Tamer; van Soest, Rob W.m. (Zootaxa, 2005)
Amphimedon (Porifera, Demospongiae, Haplosclerida, Niphatidae), a pantropical genus of reef and mangrove sponges, was recently recorded for the first time from the Red Sea suggesting a rarity which is not sustained by new reef surveys in the Gulf of Aqaba. Here we describe four species of Amphimedon occurring commonly in the Gulf of Aqaba. Among these, three are new to science, A. dinae sp.nov., A. jalae sp.nov. and A. hamadai sp.nov., the fourth one has been recently described as A. chloros Ilan et al., 2004. Although the latter species and our three new species are the first definite Ampimedon species recorded from the Red Sea, at least one previously described sponge from the region, Ceraochalina ochracea Keller, 1889 is suspected to belong to this genus as well. The status of the described and suspected Red Sea Amphimedon is discussed and compared to species recorded from neighbouring Indian Ocean waters.